Optimal adjuvant therapy in clinically N2 non-small cell lung cancer patients undergoing neoadjuvant chemotherapy and surgery: The importance of pathological response and lymph node ratio. (July 2019) - Shinde, Ashwin; Horne, Zachary D.; Li, Richard; Glaser, Scott; Massarelli, Erminia; Koczywas, Marianna; Erhunmwunsee, Loretta; Reckamp, Karen L.; Weksler, Benny; Salgia, Ravi; Beriwal, Sushil; Amini, Arya
Highlights: Pathological downstaging after neoadjuvant chemotherapy affects survival in NSCLC. Adjuvant therapy does not benefit patients with ypN0-1 or lymph node ratio < 15%. Adjuvant chemotherapy and radiation benefit ypN2 and lymph node ratio > 15%. The results may provide guidance in the absence of randomized trials. Abstract: Objectives: Optimal adjuvant therapy in patients with clinically N2 (cN2) non-small cell lung cancer (NSCLC) who undergo neoadjuvant chemotherapy followed by surgery is controversial. We evaluated the impact of adjuvant chemotherapy (CT) and/or radiation (RT) in this patient population. Materials and methods: Patients with non-metastatic, cN2 NSCLC diagnosed from 2004 to 2015 were identified from the National Cancer Database, which captures 70% of cancer cases diagnosed in the United States. Patients underwent neoadjuvant CT and surgical resection. Patients couldn't receive RT before surgery. Survival was compared using log-rank and Cox proportional hazards modeling. Subset analyses were performed based on post-chemotherapy surgical nodal staging (ypN0-2) and lymph node ratio (LNR), including 0%, 1–15%, or >15% involvement. LNR was defined as number of nodes involved by tumor divided by number of nodes examined. Results and conclusions: We identified 1541 patients. The percentage of patients who received adjuvant CT and RT was 18.9% and 35.7% respectively. ypN status and LNR were predictive of survival on univariate analysis, but only LNR maintained significance on multivariate analysis. There was no benefit observed for adjuvant CT or RT in the entire cohort. On subset analyses, a survival benefit was observed in ypN2 patients with receipt of CT or RT (HRs 0.77 and 0.81, respectively, p < 0.05). In patients with LNR > 15%, there was a significant benefit of RT (HR 0.76, p = 0.007) and borderline benefit of CT (HR 0.78, p = 0.058). Patients with cN2 disease with subsequent ypN0-1 and/or LNR < 15% following induction chemotherapy do not benefit from adjuvant therapy. Patients with persistent N2 disease and LNR > 15% who receive adjuvant CT and RT have improved survival. Aggressive consolidative therapy appears to improve survival in patients with persistent or high nodal burden disease.